2021
DOI: 10.1021/jasms.1c00311
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Optimization of Ambient Ionization Ion Mobility Mass Spectrometry for Rapid Separation of Isomers

Abstract: Current methods typically used for metabolite screening and disease diagnosis often require extensive sample preparation, which increases analysis time and associated costs. While ambient ionization techniques enable the analysis of various samples in complex matrices with little or no sample preparation in a short time (typically within a minute), their reduced selectivity, even when coupled with high-resolution mass spectrometers, limits their application in certain fields. In this study, we have optimized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…The effluent from the RPLC separation was directed to the ESI source of the Agilent 6560 IM-QTOF MS. The instrument has been described in detail elsewhere, and the conditions for the ESI source were as follows: Drying gas temperature and flow rate, 325 °C, and 5 L/min; nebulizer gas pressure, 30 psi; sheath gas temperature and flow rate, 275 °C, and 12 L/min; capillary voltage, 3500 V; nozzle voltage, 1000 V; fragmentor, 400 V; octopole RF, 750 V. The instrument was operated in all-ion IM-MS/MS mode, with ion mobility spectra acquired using a pseudorandom 5-bit sequence (multiplexing mode). In the multiplexing mode, several ion packets are pulsed into the drift tube during each data acquisition cycle, increasing the efficiency of ion utilization within the same dwell time .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effluent from the RPLC separation was directed to the ESI source of the Agilent 6560 IM-QTOF MS. The instrument has been described in detail elsewhere, and the conditions for the ESI source were as follows: Drying gas temperature and flow rate, 325 °C, and 5 L/min; nebulizer gas pressure, 30 psi; sheath gas temperature and flow rate, 275 °C, and 12 L/min; capillary voltage, 3500 V; nozzle voltage, 1000 V; fragmentor, 400 V; octopole RF, 750 V. The instrument was operated in all-ion IM-MS/MS mode, with ion mobility spectra acquired using a pseudorandom 5-bit sequence (multiplexing mode). In the multiplexing mode, several ion packets are pulsed into the drift tube during each data acquisition cycle, increasing the efficiency of ion utilization within the same dwell time .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Then, the filter papers were cut into several triangles of approximately 8 mm base width and 10 mm height and placed at an optimal distance (∼6 mm) from the IM-MS inlet. Spray solvent and high voltage were then applied to generate an electrospray-like plume . Forty microliters of the spray solvent were added, which enabled the extraction of various analytes and efficient paper spray ionization.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…188 The additional separation technology can significantly improve the selectivity by effectively reducing the background noise, thus increasing the detection limit by 5−10 times. Olajide et al 197 optimized the ionization and transmission parameters of PSI-IM-MS, demonstrated the separation of geometric isomers and structural isomers, and developed a leaf spray ionization IM-MS platform, which can quickly analyze pesticide isomers in leaf matrix. In addition, they introduced a new method to measure the single-field CCS, and the difference between CCS and traditional steped-field and single-field methods was only 0.15% and 0.25%, respectively, which improved the reliability of compound identification.…”
Section: And Characterization Of Small Moleculesmentioning
confidence: 99%
“…In comparison to other techniques, such as LTP‐MS and ESI‐IMS, similar LODs could be achieved for a number of target analytes, including codeine, papaverine, and caffeine. In a similar vein, PS and leaf spray ionization techniques were also coupled with ion mobility and MS 197 . In coupling these techniques, the authors demonstrated the ability to separate isomeric pesticides and lipids, reduce the effects of matrix effects, and improve the signal‐to‐noise of target analytes.…”
Section: Applications Of Aimsmentioning
confidence: 99%